EFEKTIVITAS MEDIA PEMBELAJARAN DIGITAL DALAM MENGEMBANGKAN KETERAMPILAN BERTANYA KRITIS PADA SISWA SEKOLAH DASAR: SUATU STUDI LITERATUR - Rachmah , Fathiyah; Najwa laika Putri Abdi; Niken Widy Astuti; Putra , Farhan Dwi Syah; Dewina , Zulfa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to analyze the effectiveness of digital learning media in developing critical questioning skills among elementary school students through a systematic literature review. A systematic literature review approach with a modified PRISMA protocol was employed to examine ten selected articles from Sinta-accredited national journals published between 2020-2024. The analysis revealed four main themes: (1) effective digital learning media characteristics including interactivity, multimodal content presentation, contextuality, and features supporting independent exploration; (2) optimal implementation strategies encompassing character education integration, Socio Scientific Issues approach, structured mentoring, and variation and combination of various types of learning media; (3) factors influencing effectiveness including teacher competence, learning environment support, and individual student characteristics; and (4) implementation challenges in the form of technology access gaps, passive use tendencies of digital media, and difficulties in evaluating the quality of critical questions. Recommendations include developing media based on instructional design that targets critical questioning skills, enhancing teacher competence, and integrating digital media with active learning strategies. Implementing these recommendations requires collaboration among various educational stakeholders to optimize the utilization of digital learning media in developing critical questioning skills among elementary school students.